PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS DAN KETERAMPILAN BELAJAR SISWA SMP DENGAN MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING - Laelasari Laelasari; Euis Eti Rohaeti; Nelly Fitriani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
The purpose of this study is to examine how the improve mathematical communication ability of students in learning using contextual approach. The research method used in this study is a quasi-experimental method, with two different classes taken, where the first class gets the learning with the Contextual Approach and the second class using ordinary learning. The population is all students in one of the islamic junior hight schools in Cimahi city with a sample taken two classes. Both classes were given pretest and early questionnaires to determine their initial ability, then the experimental class was given learning with the contextual approach and the control class was given regular learning, and at the end of both classes were given postes that will on though to use help software SPSS 22 and Minitab 16. Analysis using Product Moment Pearson. The results showed a significan students in learning mathematics.